Teoria e prática no processo de formação profissional: o caso de um curso de licenciatura em matemática - Leal, Maria de Fatima Costa (2016)
This study was carried out under the Graduate Program in Mathematics Education of the Pontifícia Universidade Católica de São Paulo as part of the Research Project "Curricular Development in Mathematics and Teacher Training". We sought to further studies exploring the forms of coordination between the ‘theory’ and ‘practice’ dimensions proposed and developed in the Political-Pedagogic Project (PPP) of a teaching certification program in Mathematics in Bahia state. To this end, the following research questions were addressed: Does the program described in the PPP have mechanisms for coordinating theory and practice? What kinds of implicit and formalized knowledge envisaged in the PPP help the student to acquire practical knowledge of teaching? What do students at different stages of the program disclose regarding the knowledge provided by the syllabus? The nature of the information collected and the methods adopted for its treatment characterize this research as a qualitative study of the case-study type. The theoretical references – Fiorentini (2005), Schön (2000), Tardif (2000) and Candau and Lelis (1999) – were chosen to provide tools that would help produce the research report. The PPP for the teaching certification program in Mathematics of the Universidade do Estado da Bahia was initially employed as the information source. In addition, the study drew on the statements of nine students who had completed at least half of the program and, from their reports, we sought to identify to what extent the proposals contained in the PPP enabled or otherwise the inter-relationship between theory and practice. Treatment of the information collected showed that the introductory texts from the PPP for the teaching certification program in Mathematics reiterated the importance of coordinating theory and practice in teacher training, thereby complying with the resolutions outlined in law. However, the examples of coordination between theory and practice did not favor the relationship of unity advocated in the curriculum proposed in the PPP. The mechanisms employed to promote this coordination exhibited inherent weaknesses, particularly regarding the inclusion of practice as a curricular component. The statements of the students interviewed indicated that, despite a curriculum organized into different aspects of training, there was a predominance of practical activities which served only to apply the theories studied during the program. More specifically, according to the students, the program syllabus favors and reaffirms the dichotomy between theory and practice. In conclusion, we believe that one of the main contributions of this research report lies in the fact that the students, through their discourse, have provided insights on the relationship between theory and practice outlined in the PPP for the program. These insights are revealed amid a concern held by students of not perceiving themselves as future teachers who are confident and prepared to commence professional practice